Implementation of Digital Literacy Movement through The Alkapay (E-Money) Program - Fitriani, Aryan Febbylia; Torre, Adolph Ian A. Dela (Nur Science Institute, 2024)
Background:This study aims to determine 1) the implementation of the digital literacy movement in the AlkaPay (e-money) program at SDIT Muhammadiyah Al-Kautsar Gumpang, 2) Describe the advantages of implementing the digital literacy movement through the AlkaPay (e-money) program at SDIT Muhammadiyah Al-Kautsar Gumpang, 3) Describe the obstacles to implementing the digital literacy movement through the AlkaPay (e-money) program at SDIT Muhammadiyah Al-Kautsar Gumpang Method:The type of research that will be used by researchers is included in descriptive research with a qualitative approach. The presence of researchers in this qualitative research, researchers act as instruments and as collectors of research data. Data collection techniques in this study use interview and documentation techniques. The validity of the data used by researchers in this study is technical triangulation. The data analysis technique used in this study, researchers use qualitative descriptive research analysis. Result:. Based on the results of the study, it can be concluded that the implementation of the digital literacy movement through the AlkaPay (e-money) program at SDIT Muhammadiyah Al-Kautsar Gumpang was carried out by holding socialization. The advantages of implementing the digital literacy movement through the AlkaPay program are increasing student knowledge and increasing student understanding regarding the use of AlkaPay cards, and obstacles to implementing the digital literacy movement through the AlkaPay program are that lower-class students have a low level of understanding. Implication:This study is the importance of integrating digital literacy in basic education to prepare a generation that is technologically literate and able to optimize the use of e-money in everyday life. The findings show that the AlkaPay program can improve students' digital knowledge and skills, but there are still challenges in terms of understanding, especially in lower grade students.